East Coast fever (ECF)-1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Dr Hildah Lumbwe, Department of Veterinary and Livestock Development, Zambia. The interview looks at symptoms, treatment and prevention.